CURRICULUM MANAGEMENT IN SHAPING THE CHARACTER OF STUDENTS OF MAN 1 MUSI RAWAS - Ahmad Sayfudin (Media Inovasi Pendidikan dan Publikasi, 2024)
MAN 1 Musi Rawas is a faith-based educational institution and is able to exist and compete with public schools and has students with good character so that it becomes a magnet for the community to join MAN 1 Musi Rawas. The purpose of this study is to (1) describe and analyze curriculum management in shaping the character of students in Madrasah Aliyah Negeri 1 Musi Rawas and (2) know the character of students in Madrasah Aliyah Negeri 1 Musi Rawas. This research uses a qualitative type of research with a case study approach. The object of this research was carried out at MAN 1 Musi Rawas. Data collection techniques using Observation, Interviews, and Documentation. Data sources in this study include the Head of Madrasah, Deputy Head of Madrasah for Curriculum, Deputy Head of Madrasah for Student Affairs, teacher council, TU staff, students and the community. Analysis techniques in this study are data collection, data reduction, data presentation, conclusions. The triangulation used to test the validity of data is the triangulation of techniques and sources. The results showed that (1) Curriculum Management in Shaping the Character of MAN 1 Musi Rawas Students consisted of: 1) Curriculum planning. 2) Organizing consists of intracurricular and extracurricular. 3) Implementation of the curriculum. 4) Curriculum evaluation. (2) Character of MAN 1 Musi Rawas students 1) Religious Values, learners. 2) Value discipline. 3) The Value of Social Care.